Berechnung von Thermospannungen in Wärmebehandlungsanlagen mittels gekoppelter numerischer Verfahren1. Issue 8 (21st June 2013) - Lenz, Wolfgang; Pfeifer, Herbert; Wessling, Matthias
<x xml:space="preserve">Abstract</x> Strip floatation furnaces are used for heat treatment of metal products that are too sensitive to be allowed to have any mechanical contact at high temperatures. Nowadays increasing the process temperature is often the only way to fulfill the high standards concerning efficiency and productivity. Most constructional measures that are used in low and medium temperature applications do not have the same beneficial effect for high temperature applications. Since many thermal effects are not taken into account by a structural analysis, these effects are often underestimated by classical finite element simulations. This paper presents the use of an innovative, easy‐to‐use method to increase the accuracy of stress simulations used during the design process of high temperature furnaces, by including effects caused by the thermal conditions.